Biomechanical Comparison of Two Pediatric Blade Plate Designs in Proximal Femoral Osteotomies. Issue 1 (February 2020) - Ruzbarsky, Joseph J.; Swarup, Ishaan; Garner, Matthew R.; Meyers, Kathleen N.; Edobor-Osula, Folorunsho; Widmann, Roger F.; Scher, David M.
Background: Blade plates are frequently used for internal fixation following proximal femoral varus rotational osteotomy to treat hip dysplasia in children with cerebral palsy. Recently, cannulated blade plates with the option for a proximal locking screw have demonstrated ease of insertion and low complication rates. Although there are two commonly used blade plates with a proximal screw option, no comparison of their biomechanical profiles has been undertaken. Questions/Purposes: Our study sought to compare the structural properties under axial loading, as well as the biomechanical contribution of a proximal screw, of two different 90° cannulated blade plates designed for pediatric proximal femurs. Plate A has a hole distal to the blade designed to attach a plate inserter, through which a 3.5-mm non-locking cortical screw could be placed. Plate B has a threaded hole distal to the blade designed to accept a 3.5-mm locking screw. Methods: Plate A and plate B were inserted into 33 left pediatric synthetic proximal femurs. Axial loading to failure of plate A with and without a proximal screw was compared to that of plate B with and without a proximal screw. An additional 10 samples using plate B, with and without a proximal locking screw, were tested in tension to quantify the effect of the proximal screw on pullout strength. Results: Plate B failed at a higher axial load than plate A. The addition of a proximal screw did not affect the axial load to failure for either plate. Pullout testing revealed that blade plates fixed with the proximal screw failed in tension at a significantly higher load (856.3 ± 120.9 N) than those without proximal fixation (68.1 ± 9.3 N, p  < 0.001). Conclusions: Plate B failed at a higher axial load in biomechanical testing, likely related to differences in its design. The addition of a proximal screw did not increase the axial loading properties of the blade plate construct but did increase the pullout strength by a factor of 12. These results may be used to influence implant selection and post-operative rehabilitation following proximal femoral osteotomies in children.